Artist/Animal - Baker, Steve (Minneapolis : University of Minnesota Press, 2013)
"Animals have always been compelling subjects for artists, but the rise of animal advocacy and posthumanist thought has prompted a reconsideration of the relationship between artist and animal. In this book, Steve Baker examines the work of contemporary artists who directly confront questions of animal life, treating animals not for their aesthetic qualities or as symbols of the human condition but rather as beings who actively share the world with humanity.The concerns of the artists presented in this book--Sue Coe, Eduardo Kac, Lucy Kimbell, Catherine Chalmers, Olly and Suzi, Angela Singer, Catherine Bell, and others--range widely, from the ecological to the philosophical and from those engaging with the modification of animal bodies to those seeking to further the cause of animal rights. Drawing on extensive interviews he conducted with the artists under consideration, Baker explores the vital contribution that contemporary art can make to a broader conception of animal life, emphasizing the importance of creativity and trust in both the making and understanding of these artworks.Throughout, Baker is attentive to issues of practice, form, and medium. He asks, for example, whether the animal itself could be said to be the medium in which these artists are working, and he highlights the tensions between creative practice and certain kinds of ethical demands or expectations. Featuring full-color, vivid examples of their work, Artist Animal situates contemporary artists within the wider project of thinking beyond the human, asserting art's power to open up new ways of thinking about animals. "--
boek